IFLA WLIC 2018 volunteers: sharing experience from social media assistant team / Nurul Diana Jasni … [et al.] - Jasni, Nurul Diana; Ismail, Mohd Ikhwan; Zilah, Amirul Firdaus; Hamzah, Mohd Faizal (2020)
Social media is playing an important role to be the most significant mediocre for marketing, communicating and indorsing. A proper task force team on social media may lead to systematic social media content during the event or any activities. The job scope of the social media team should assimilate with the content expert, photography, broadcasting, copywriter, editing skills and many more. Social media content also should be aligned with the need for copyright and ethical issues. In many ways, complete social media experts should skilful and sensitive to current issues. Each of the tasks will ensure the quality of social media content. Therefore, this paper will present the experience from the IFLA WLIC 2018 social media team. The objective of this conceptual paper is to share the structure of the job scope of the social media team, including the scheduling, quality checking, medium, job scope numerous more. Not only that, the intention of this paper also is to provide a proper guideline on social media setup for any libraries and information centre in Malaysia. Constructed based on literature search and observation, there is no comprehensive social media task force had been developed in any libraries in Malaysia. Hence, this knowledge sharing on IFLA WLIC 2018 social media team might give an idea for the social media task force in any libraries and information centres in Malaysia. Besides presenting the challenge of the IFLA WLIC 2018, few recommendations on the social media task force team are also documented for future improvement.